2012
DOI: 10.4103/0019-5359.110865
|View full text |Cite
|
Sign up to set email alerts
|

The role of psychiatric symptoms, alexithymia, and maladaptive defenses in patients with functional dyspepsia

Abstract: Psychiatric symptoms, alexithymia, and maladaptive defense play significant role in the emergence of FD symptoms. This study proposes that FD patients should be evaluated and treated by departments of gastroenterology and psychiatry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…When considered categorically by using the suggested TAS-20 cut-off scores (Taylor et al, 1997 ), the prevalence of alexithymia was 66% ( n = 80) in the FGID, 38% ( n = 44) in the IBD, and 4.5% ( n = 5) in the control groups (χ 2 = 94.94, p < 0.001). Similarly, it was found that 60 FD patients scored significantly higher than 60 controls on the total (61.58 ± 6.56 vs. 47.50 ± 8.30) as well as the DIF (27.45 ± 4.31 vs. 17.52 ± 4.47) and DDF (17.22 ± 4.10 vs. 13.00 ± 3.74) subscales, even after multiple adjustments ( F = 106.16; p < 0.001) (Faramarzi et al, 2012 ). By contrast, there was no statistically significant difference between groups on the EOT factor of the TAS (16.92 ± 3.51 vs. 16.98 ± 3.31; t -test; p = 0.915).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…When considered categorically by using the suggested TAS-20 cut-off scores (Taylor et al, 1997 ), the prevalence of alexithymia was 66% ( n = 80) in the FGID, 38% ( n = 44) in the IBD, and 4.5% ( n = 5) in the control groups (χ 2 = 94.94, p < 0.001). Similarly, it was found that 60 FD patients scored significantly higher than 60 controls on the total (61.58 ± 6.56 vs. 47.50 ± 8.30) as well as the DIF (27.45 ± 4.31 vs. 17.52 ± 4.47) and DDF (17.22 ± 4.10 vs. 13.00 ± 3.74) subscales, even after multiple adjustments ( F = 106.16; p < 0.001) (Faramarzi et al, 2012 ). By contrast, there was no statistically significant difference between groups on the EOT factor of the TAS (16.92 ± 3.51 vs. 16.98 ± 3.31; t -test; p = 0.915).…”
Section: Resultsmentioning
confidence: 98%
“…Most studies on FGID had a cross-sectional design (Arun, 1998 ; Porcelli et al, 1999 ; Porcelli and De Carne, 2001 ; Weinryb et al, 2003 ; Van Oudenhove et al, 2008 ; Van Oundenhove et al, 2011a ; Faramarzi et al, 2012 ; Mazaheri et al, 2012 ; Bengtsson et al, 2013 ) and control groups were formed of healthy subjects (Arun, 1998 ; Porcelli et al, 1999 ; Faramarzi et al, 2012 ; Mazaheri et al, 2012 ). The first study investigating alexithymia with the original TAS-26 (Taylor et al, 1985 ) in a sample of 30 IBS patients showed they had higher levels of alexithymia (125.96 ± 11.5) than a control group of 30 matched healthy subjects (108.96 ± 13.29) ( t = 20.04; p < 0.01) (Arun, 1998 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It refers to a personality trait associated with difficulties with identifying or describing feelings, mental imaging and fantasy, and external cognitive orientation [1]. Research has revealed that alexithymia is associated with psychiatric disorders, such as psychosomatic disorders [24], depression [5], and anxiety [6]. Some studies have reported a positive relationship between alexithymia and pain disorders [7, 8].…”
Section: Introductionmentioning
confidence: 99%